Nrf1 acts as a highly-conserved determinon for maintaining robust redox homeostasis in the eco-evo-devo process of life histories - Yiguo Zhang; Xi Chen; Meng Wang; Yuping Zhu; Wei Shi; Chao Li; Zhengwen Zhang; Hiroaki Taniguchi; Ping Ao (Cell Stress, 2025)
Differential and even opposing functions of two major antioxidant transcription factors Nrf1 and Nrf2 (encoded by Nfe2l1 and Nfe2l2, respectively) are determined by distinctions in their tempospatial positioning, topological repartitioning, proteolytic processing, and biochemical modification, as well as in their shared evolutionary origin. As a matter of fact, the allelopathic potentials of Nrf1 and Nrf2 (both resembling two entangled ‘Yin-Yang’ quanta that comply with a dialectic law of the unity of opposites) are fulfilled to coordinately control redox physiological homeostasis so as to be maintained within the presetting thresholds. By putative exponential curves of redox stress and intrinsic anti-redox capability, there is inferable to exist a set point at approaching zero with the ‘Golden Mean’ for the healthy survival (i.e., dubbed the ‘zero theory’). A bulk of the hitherto accumulating evidence demonstrates that the set point of redox homeostasis is dictated selectively by multi-hierarchical threshold settings, in which the living fossil-like Nrf1 acts as a robust indispensable determinon, whereas Nrf2 serves as a versatile chameleon-like master regulon, in governing the redox homeodynamic ranges. This is attributable to the facts that Nrf2 has exerted certain ‘double-edged sword’ effects on life process, whereas Nrf1 executes its essential physiobiological functions, along with unique pathophysiological phenotypes, by integrating its ‘three-in-one’ roles elicited as a specific triplet of direct sensor, transducer and effector within multi-hierarchical stress responsive signaling to redox metabolism and target gene reprogramming. Here, we also critically reviewed redox regulation of physio-pathological functions from the eco-evo-devo perspectives, through those coding rules (redox code, stress-coping code, and topogenetic code). The evolving concepts on stress and redox stress were also further revisited by scientific principles of physics and chemistry. Besides, several novel concepts such as oncoprotists, Reverse Central Dogma, and Grand Redox-Unifying Theory’ (GRUT) of life, together with diffusive reactive species (DRS)-based murburn concept integrating all stochastic electron-, proton- and/or moiety-transfer reactive and interactive processes (e.g., PCHEMS), are introduced in this interdisciplinary and synthetic review.